147 Within-Family Dynamics Influencing Parent and Child Sleep Quality and Nighttime Activities. (3rd May 2021) - Hanley, Brigid; Gorovoy, Suzanne; Chamberlain, Stihlyn; Bhushan, Bharat; Ghani, Sadia; Killgore, William D S; Wills, Chloe; Grandner, Michael
Abstract: Introduction: Increasing efforts have focused on child sleep due to its benefits to academics and physical/mental health. Less understood are the within-family dynamics that drive sleep-related behavior. Methods: Data were obtained from the 2014 National Sleep Foundation Sleep in America Poll (N=1102 parent/child dyads). Variables including age, gender, sleep quality (Excellent/Good/Fair/Poor), evening activities including reading, TV-watching, and online browsing/gaming (Never/Rarely/Sometimes/Often) were reported for parent and child. Ordinal logistic regressions examined child nighttime activity as outcome and nighttime activities (entered simultaneously in the model, adjusted for each other) as independent variables, adjusted for parent and child age, sex, and sleep quality. Results: Worse sleep quality in parents was associated with worse sleep quality in their children. Moreover, increased likelihood of child television-watching at night was not associated with parental sleep quality, but it was associated with child sleep quality, with "Fair" and "Poor" sleepers more likely to watch TV (Fair: oOR=1.7, p=0.018; Poor: oOR=8.0, p=0.001). Child television-watching was not associated with likelihood of parental reading, but it was associated with likelihood of parental online browsing/gaming (Rarely oOR=1.7, p=0.001; Sometimes oOR=2.3, p<0.0005; Often oOR=1.9, p=0.004) and parental TV-watching (Rarely oOR=2.6, p<0.0005; Sometimes oOR=5.4, p<0.0005; Often oOR=13.3, p<0.0005). Child online browsing/gaming was also not associated with parental sleep quality but it was associated with child sleep quality (Fair oOR=2.3, p=0.001; Poor oOR=4.8, p=0.009) and parental reading (Rarely oOR=1.5, p=0.04; Often oOR=1.6, p=0.03), TV-watching (Rarely oOR=2.3, p=0.004; Sometimes oOR=2.8, p<0.0005; Often oOR=4.6, p<0.0005) and online browsing/gaming (Rarely oOR=2.8, p<0.0005; Sometimes oOR=5.0, p<0.0005; Often oOR=7.8, p<0.0005). Child reading was not associated with parent or child sleep quality or parental online browsing/gaming, but it was related to parental TV-watching (Sometimes oOR=1.45, p=0.04; Often oOR=1.6, p=0.02) and reading (Rarely oOR=2.4, p<0.0005; Sometimes oOR=4.4, p<0.0005; Often oOR=6.9, p<0.0005). Conclusion: Children who do not sleep well have parents who do not sleep well. Further, parents who read are more likely to have children who read, and parents on screens are more likely to have children on screens. Interventions targeted to parents may lead to better sleep habits in children. Support (if any):